Distinguishing Syntactic Markers From Morphological Markers. A Cross-Linguistic Comparison - Weth, Constanze (Frontiers in Psychology, 2020)
This brief review summarizes findings about syntactic markers, i.e. graphemic elements that indicate syntactic relations, such as inflection morphemes. Current spelling models subsume inflection with derivation and stem alternations under “morphological spellings”. They hence consider inflection only in relation to the orthographic word. This paper argues that syntactic markers are a specific category as they are part of the orthographic word but also systematically tied to the presence of syntactic features above the word level. Syntactic spelling refers thus not only to the correct spelling of a syntactic marker but to its correct application within a given syntactical context. In syntactic reading, readers must notice the marker and interpret it correctly to understand the sentence. Syntactic spelling and reading have hence been found to be highly demanding in many languages. Syntactic information is not decisive for sentence understanding in many cases, since the information can be deduced from the context. In order to focus the definition of syntactic markers, this paper restricts them to those graphemic elements that convey syntactical but no lexical features and are further unrelated to phonology. The paper concludes that syntactic markers and spelling should be distinguished from morphological spelling. Examples are given for English, French, Dutch and German